Partial response or better at six months is prognostic of superior progression‐free survival in Waldenström macroglobulinaemia patients treated with ibrutinib. (18th November 2020) - Castillo, Jorge J.; Abeykoon, Jithma P.; Gustine, Joshua N.; Zanwar, Saurabh; Mein, Kirsten; Flynn, Catherine A.; Demos, Maria G.; Guerrera, Maria L.; Kofides, Amanda; Liu, Xia; Munshi, Manit; Tsakmaklis, Nickolas; et al.
Summary: Ibrutinib is associated with durable responses in patients with Waldenström macroglobulinaemia (WM). We hypothesized that response depth is predictive of progression‐free survival (PFS) in WM patients treated with ibrutinib. Using landmark analyses, we evaluated response depth in two cohorts of WM patients treated with ibrutinib monotherapy. The learning cohort was composed of 93 participants from two clinical trials, and the validation cohort of 190 consecutive patients treated off clinical trial. Rates of partial response (PR) or better at six months in learning and validation cohorts were 64% and 71% respectively ( P = 0·29). In the learning cohort, three‐year PFS rates for patients who attained PR or better at six months versus not were 81% and 57% respectively ( P = 0·009). In the validation cohort, three‐year PFS rates for patients who attained PR or better at six months versus not were 83% and 54% respectively ( P = 0·008). In multivariate analyses, attaining PR or better at six months was associated with superior PFS in the learning [hazard ratio (HR) 0·38; P = 0·01] and validation cohorts (HR 0·18; P = 0·004). Attaining PR at six months on ibrutinib emerges as an intermediate outcome of interest and should be validated as surrogate for PFS in clinical trials evaluating Bruton tyrosine kinase inhibitors in WM.